Photographing waterdrops exploring macro worlds with Harold Davis - Davis, Harold, 1953- (Waltham, MA : Focal Press, 2012)
"How to shoot waterdrops with a macro lens"--
All age.
Keywords: Macrophotography; Photography of water; Drops -- Pictorial works